A comparison of physical and technical performance profiles between successful and less-successful professional rugby league teams - Kempton, T.; Sirotic, A. C.; Coutts, A. J. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To examine differences in physical and technical performance profiles using a large sample of match observations drawn from successful and less-successful professional rugby league teams.